2010
DOI: 10.1074/jbc.m110.141317
|View full text |Cite
|
Sign up to set email alerts
|

GATA Proteins Work Together with Friend of GATA (FOG) and C-terminal Binding Protein (CTBP) Co-regulators to Control Adipogenesis

Abstract: GATA transcription factors have been implicated in controlling adipogenesis in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…TFs of GATA binding proteins have been found to serve as negative regulators of adipocyte formation [24,25]. GATA-2, a member of GATA binding protein family, suppresses adipocyte differentiation [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TFs of GATA binding proteins have been found to serve as negative regulators of adipocyte formation [24,25]. GATA-2, a member of GATA binding protein family, suppresses adipocyte differentiation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ plays key roles in promoting adipocyte differentiation [23] and in inhibiting HSC activation [2]. In contrast, GATA proteins serve as the negative regulators of adipocyte formation [24,25]. Since leptin treatment reduced PPARγ expression in HSCs [14,15], it was interesting to investigate whether GATA proteins bound to the potential GATA protein binding site in PPARγ1 promoter and mediated leptin inhibition of PPARγ1 expression in HSCs.…”
Section: Leptin Response Elements Exist Between Position −2333 and −2mentioning
confidence: 98%
“…However, the finding should be interpreted with caution, since there is a possibility that aberrations in fragile sites are secondary to metabolic stress during clonal expansion. Two other genes were also partly deleted: NEGR1 encodes a protein involved in neurite outgrowth [26,27], and ZFPM2 engaged in hematopoiesis and cardiogenesis [28]. Alterations in these genes have not been specifically reported or probed for in a WT context before, and we can only speculate on the significance of the discovered microdeletions for the development of the tumor investigated in this study.…”
Section: Discussionmentioning
confidence: 91%
“…In 3T3-L1 cells, FOG2 is shown to control adipogenesis (15), a key process that determines the mass of adipose tissue. These results are consistent with other studies that showed FOG2 to be an important regulator for development in various tissues (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FOG2 expression is increased in liver of insulin-resistant mice induced by interleukin-6 injection or with mutation in leptin receptor (db/db) (14). Moreover, overexpression of FOG2 blocks adipogenesis (15), a process closely related to lipid metabolism (16). Although FOG2 expression is not that abundant in normal liver (7,9), hepatic FOG2 may play an important role in the regulation of insulin sensitivity and lipid metabolism.…”
mentioning
confidence: 99%